Developmental Outcome of Preterm Infants with Severe Intraventricular Hemorrhage - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
Of 214 preterm infants studied at Wilhelmina Children's Hospital, Utrecht, the Netherlands, 94 (44%) had a grade 111 intraventricular hemorrhage (1VH), and 120 (56%) had a grade IV hemorrhage.